The Development of Interactive Multimedia Learning in Information and Communication Technology Subjects - Syahputra, Frandrio; Maksum, Hasan (Journal of Education Research and Evaluation, 2020)
Learning media is an important learning component. Therefore, teachers must able to develop instructional media that can improve student abilities. One of the learning media that supports these goals was interactive multimedia. This study aimed to develop valid, practical, and effective interactive multimedia learning on Information and Communication Technology subjects. This research was research and development. The development model used was a 4-D model, which consists of defining, designing, developing, and disseminating stages. The defined stage was carried out with curriculum analysis, material analysis, and student analysis. The design stage was carried out by designing the learning media. At the development stage, validity tests were carried out through validation sheets of learning media, practicality tests through media application observation sheets, teacher and student response questionnaires, effectiveness tests obtained from the knowledge competency assessment. The disseminated stage was carried out by spreading the device. The analysis results showed that the Interactive learning media in Information and Communication Technology subjects have been tested and got a valid score (89.25%), according to the teacher's response (90.23%) in very practical category, students’ response (90.09%). The response was in the very practical category. With this score, interactive multimedia is categorized as practical and effective learning media.